Inhibition of HMGB1-induced angiogenesis by cilostazol via SIRT1 activation in synovial fibroblasts from rheumatoid arthritis. - Hye Young Kim (Public Library of Science (PLoS), 2014)
High mobility group box chromosomal protein 1 (HMGB-1) released from injured cells plays an important role in the development of arthritis. This study investigated the anti-angiogenic effects of cilostazol in collagen-induced arthritis (CIA) of mice, and the underlying mechanisms involved. The expressions of HIF-1α, VEGF, NF-κB p65 and SIRT1 in synovial fibroblasts obtained from rheumatoid arthritis (RA) patients were assessed by Western blotting, and in vitro and in vivo angiogenesis were analyzed. Tube formations by human microvascular endothelial cells (HMVECs) were significantly increased by direct exposure to HMGB1 or to conditioned medium derived from HMGB1-stimulated RA fibroblasts, and these increases were attenuated by cilostazol, the latter of which was blocked by sirtinol. HMGB1 increased the expression of HIF-1α and VEGF and concomitantly increased nuclear NF-κB p65 and DNA binding activity, but these effects of HMGB1 were inhibited by cilostazol. SIRT1 protein expression was time-dependently decreased (3-24 hr) by HMGB1, which was recovered by pretreatment with cilostazol (1-30 µM) or resveratrol, accompanying with increased SIRT1 deacetylase activity. In the tibiotarsal joint tissues of CIA mice treated with vehicle, HIF-1α- and VEGF-positive spots and CD31 staining were markedly exaggerated, whereas SIRT1 immunofluorescence was diminished. These variables were wholly reversed in cilostazol (30 mg/kg/day)-treated mice. Furthermore, number of blood vessels stained by von Willebrand factor antibody was significantly lower in cilostazol-treated CIA mice. Summarizing, cilostazol activated SIRT1 and inhibited NF-κB-mediated transcription, thereby suppressing the expression of HIF-1α and VEGF. In addition, cilostazol caused HIF-1α deacetylation by enhancing SIRT1 activity and reduced VEGF production, thereby had an anti-angiogenic effect in vitro studies and in CIA murine model.